Metabolic responses of Chlamydomonas reinhardtii CC125 under different proportions of urea and ammonium - Batista, Aline Duarte (2017)
Chlamydomonas reinhardtii (phylum Chlorophyta) as a model organism for nitrogen (N) starvation studies in order to evaluate lipid accumulation, changes in bioenergetics and the regulation of photosynthesis. Chlorophytes can incorporate N in inorganic or organic form and the source of N influences the accumulation of lipids. The most frequently available inorganic sources are Ammonium (NH 4+ ), Nitrate (NO 3- ) and Nitrite (NO 2- ) and the most common organic sources are purines, urea and amino acids. Use of urea in others chlorophytes usually promotes enhancement in both growth, lipid production and biomass when compared to NH 4+ . However, for C. reinhardtii there is a lack of more specific information on how their metabolism responds to the assimilation of N organic sources. Thus, in this work we studied the metabolism and growth of C. reinhardtii CC125 in urea as the only N source as well as combined with NH 4+ . Aliquots of C. reinhardtii CC125 were maintained in mixotrophic growth in TAP (Tris-Acetate-Phosphate) medium under temperature between 24±2 ° C, photoperiod of 16:8 h (light: dark), 90 μmol photons m -2 s -1 and constant shaking of 110 rpm. Five treatments were carried out: (i) 100% NH 4+ (0,4 g L -1 NH 4 Cl); (ii) 25% urea (0,3 g L -1 NH 4 Cl and 0,11 g L -1 urea); (iii) 50% urea (0,2 g L -1 NH 4 Cl and 0,21 g L -1 urea); (iv) 75% urea (0,1 g L -1 NH 4 Cl and 0,32 g L -1 urea); and (v) 100% urea (0,42 g L -1 urea). The treatments were evaluated in the logarithmic phase (LOG), after 50 hours of growth and in the stationary phase (STA), after 240 hours of growth. The number of cells, cell area, ash-free dry weight, chlorophyll a and b contents, amino acids, starch, proteins, total carbohydrates and lipids were determined at LOG and STA phases. The metabolic profile and fatty acids profile was determined at STA phase. The growth observed in medium with urea was similar to 100% NH 4+ by comparing growth curves and kinetic growth. The number of cells after in LOG and STA phase was higher in treatments with lower percentage of urea. Determination of total chlorophyll a and b, free amino acids and proteins showed no differences between treatments in the LOG phase. At STA phase level of total chlorophyll as well as chlorophyll a were higher in 75 and 100% urea. The levels of chlorophyll b and total soluble proteins increased with increasing urea. The levels of carbohydrates, in the LOG phase, were higher in 100% urea treatment. In the STA phase, the highest values were observed for 100% urea and 100% NH 4+ treatments. 100% urea treatment produced more lipids than other treatments in the two growth phases. Quantification of sugars indicated that disaccharides increased in treatments with more than 75% urea. Out of 14 quantified organic acids, 11 decreased in the treatment with 25% of urea as well many amino acids. Four intermediates of TCA cycle (citrate, isocitrate, succinate and malate) increased in the treatment with 100% urea. The FAMEs profile of C. reinhardtii was altered by concentration of NH 4+ and urea: Total saturated fatty acids (ΣSFA) increase with amount of urea; however, total monounsaturated fatty acids (ΣMUFA) decrease with amount of urea. The most abundant fatty acid observed was palmitic acid (C16:0) which there is a tendency to increased with the amount of urea in the medium. The percentage of oleic acid (C18:1 w8) decreased with amount of urea, while percentages of linoleic acid (C18:2 w6) doubled in treatments containing urea. Thus, our data indicate that higher the availability of urea, higher are the Carbon (C) and N metabolism changes, without, however, promoting drastic changes in growth. In addition, our results suggest that urea might also provide additional C, altering C:N ratio in medium and lead changes in lipids and total fatty acid production and profile.